Layer-by-layer coated molecular-imprinted solid-phase microextraction fibers for the determination of polar compounds in water samples. Issue 96 (3rd October 2016) - Zhang, Maosheng; Huang, Jiarong
Abstract : In this study, the selective extraction of polar compound in water samples was reported using molecular-imprinted solid-phase microextraction (MISPME) combined with dispersive liquid–liquid microextraction (DLLME) with in situ derivatization. Abstract : In this study, a novel technique was reported for the selective extraction and analysis of polar compound in water samples using molecular-imprinted solid-phase microextraction (MISPME) combined with dispersive liquid–liquid microextraction (DLLME) with in situ derivatization. 1, 2-Benzenediol (1, 2-BD) was used as a model compound to present the validity of novel approach of analyzing polar compounds in aqueous samples. The layer-by-layer structure MISPME fiber was first prepared using 1, 2-phenylene diacetate (1, 2-PDA, derivatization product of 1, 2-BD) as the template. Subsequently, 1, 2-BD was extracted from water samples by DLLME after in situ derivatization using acetic anhydride as a derivatization agent, dichloromethane as an extraction solvent and methanol as a disperser solvent. Finally, the derivatization product 1, 2-PDA in the extraction solvent was selectively enriched by the MISPME fiber, followed by analysis by gas chromatography-flame ionization detection (GC-FID). The preparation and extraction conditions were optimized. The method exhibited a good linear relationship in a wide range from 0.05 to 10 μg mL −1 ( r 2 = 0.9984), which indicated that the established method is applicable for the quantification of 1, 2-BD. The limit of detection (LOD) was 0.01 μg mL −1 . The precision of the method was evaluated by analyzing a standard solution of 1, 2-BD at 0.5 μg mL −1, and the RSD was 5.9%.